DMAIC applied to the production control of manufactured replacement parts: a case study in an agricultural machinery factory - Gómez, Daniel Alejandro Mantilla; Araújo, Fernando de; Santos, Aline Gonçalves do; Fonseca Júnior , Lázaro Antônio da (Brazilian Journal of Production Engineering, 2024)
The globalized and competitive world requires companies to maintain increasingly strict levels of quality and process control. The challenge of ensuring a high standard of serviceability for the customer demands that tasks be performed in a way that avoids wasting material and human resources, adding value to the final service or product. Within this context, this work aims to identify the root causes responsible for delays in the shipment of replacement parts from an agricultural machinery company to its distribution center, proposing implementations to improve the manufacturing process of these parts through the DMAIC methodology, guided by the principles of lean manufacturing.
Keywords: DMAIC; Lean Manufacturing; Control; Material Flow